Crime and punishment - Dostoyevsky, Fyodor, 1821-1881.; McDuff, David, 1945- (London : Penguin Books, 2003)
Raskolnikov, a destitute and desperate former student, commits a random murder, imagining himself to be a great man far above moral law. But as he embarks on a cat-and-mouse game with police, his conscience begins to torment him and he seeks sympathy and redemption from Sonya, a downtrodden prostitute.
Includes bibliographical references (p. [xxiii]-xxiv).
Keywords: Crime -- Fiction. -- Psychological aspects -- Russia; Fiction; Saint Petersburg (Russia) -- Fiction